Lojaliteitsbemarking van handelsbanke onder professionele gegradueerdes - Immelman, Reaan (University of the Free State, 2003)
During the last five years, the financial services sector has undergone drastic changes, resulting in a market place which is characterised by intense competition and increased deregulation. In the new market place, the occurrence of committed and often inherited relationships between a customer and the bank is becoming increasingly scarce. Current research in loyalty marketing focus primarily on product loyalty marketing and very little on loyalty marketing in the service sector. Very little research has been done in a specific market segment and the purpose of this study is to do research under professional graduates. Professional graduates is defined as graduates who graduated at the University of the Free State the past five years (1997 - 2001) in the following study fields: i) Physiotherapy ii) Medical iii) Law iv) Accounting The main objective of the study is to establish if commercial banks apply loyalty marketing under professional graduates and if professional graduates remains loyal to a commercial bank. The study can contribute in the following ways which commercial banks can use: a) Commercial banks can for the first time establish if funds spend in the professional market is justified. b) Commercial banks can also establish where to focus in terms of communication to the client. c) The infrastructure of professional graduates can be determined and the research can be used to determine marketing strategies in the professional market. d) Commercial banks established strategic business units and with this research can be determine if there is a need for a niche segment under professional graduates who apply loyalty marketing. e) For the first time it will be possible for commercial banks to measure loyalty under professional graduates. The main objective of the study was achieved through an inn depth discussion of loyalty marketing, commercial bank's marketing strategy under professional graduates and 237 questionnaires for the purpose of this research were distributed under a population of 1158 professional graduates. Telephonic research as research methodology were used and the response rate of the questionnaires answered was 20.47 %. In general an analysis of different loyalty models were done and the loyalty model of Bloemer, de Ruyter and Peeters were exclusively develop for commercial banks.
Dissertation (M.Econ. (Business Management))--University of the Free State, 2003
Keywords: Commercial banks; Loyalty marketing; Loyalty; Professional graduates; Relationship marketing; Retention marketing; Loyalty models; Servqual model; Service quality; Marketing strategies; Financial institutions -- Marketing; Banks and banking -- Customer Services; Relationship marketing -- South Africa; College graduates -- South Africa